История древней русской литературы - Водовозов Николай Васильевич (Просвещение, 1966)
Экземпляры: КХ (20140417) / Инвентарный номер: 407675 / Цена: 0.84 / Сис.шифр: 8Р1 / Авт.знак: В 62 / ГРНТИ: 17 / ББК: 83